Emotional learning selectively and retroactively strengthens memories for related events - Dunsmoor, Joseph E.; Murty, Vishnu P.; Davachi, Lila; Phelps, Elizabeth A. (Nature (London), 2015)
Initially weak episodic memories in humans can be selectively enhanced and consolidated following later emotional learning involving conceptually related information, suggesting a mechanism for how we can remember initially inconsequential information after a relevant later experience. Emotional events enhance weak memories From animal studies it has long been thought that initially weak memory traces can be subsequently strengthened following re-activation a short time later. Typically, this re-activation occurs through subsequent experience or training, enhancing the strength of the original trace. However, there has been little work exploring whether a similar mechanism exists in human subjects. Here, Elizabeth Phelps and colleagues reveal that initially weak episodic memories in humans can be selectively enhanced and consolidated following later emotional learning involving conceptually related information. This retroactive memory enhancement suggests a mechanism through which we can remember initially inconsequential information following a relevant later experience. Neurobiological models of long-term memory propose a mechanism by which initially weak memories are strengthened through subsequent activation that engages common neural pathways minutes to hours later 1 . This synaptic tag-and-capture model has been hypothesized to explain how inconsequential information is selectively consolidated following salient experiences. Behavioural evidence for tag-and-capture is provided by rodent studies in which weak early memories are strengthened by future behavioural training 2 , 3 . Whether a process of behavioural tagging occurs in humans to transform weak episodic memories into stable long-term memories is unknown. Here we show, in humans, that information is selectively consolidated if conceptually related information, putatively represented in a common neural substrate, is made salient through an emotional learning experience. Memory for neutral objects was selectively enhanced if other objects from the same category were paired with shock. Retroactive enhancements as a result of emotional learning were observed following a period of consolidation, but were not observed in an immediate memory test or for items strongly encoded before fear conditioning. These findings provide new evidence for a generalized retroactive memory enhancement, whereby inconsequential information can be retroactively credited as relevant, and therefore selectively remembered, if conceptually related information acquires salience in the future.